Catalytic and filterable polyester-filter membrane electrode with a high performance carbon foam–Fe–Co catalyst improved electricity generation and waste-water treatment in MBR–MFC1. Issue 60 (2nd July 2015) - Yu, Tingting; Liu, Lifen; Yang, Qiao; Song, Jing; Yang, Fenglin
<x xml:space="preserve">Abstract</x> Cathode membrane, made of PANI modified polyester cloth, was coated with a new and high-efficiency carbon foam–Fe–Co catalyst, which is filterable, conductive and catalytic. The power density increased 38 times.